Management today : principles and practice - Burton, Gene; Thakur, Manab (New Delhi : Tata McGraw-Hill publishing company Limited, 1995)
This book is devoted to the need of practicing managers as well as to those individuals who aspire to become managers.
Includes bibliographical references p.584-600 and index
hza 05/09/2018
Loans
Keywords: Management; Business